2015
DOI: 10.4081/ija.2015.682
|View full text |Cite
|
Sign up to set email alerts
|

Use of technical and economical parameters for evaluating dairy cow ration efficiency

Abstract: The aim of this study was the development of a model for evaluating dairy cow ration efficiency. This model took into account technical, metabolic, and economic parameters, which were divided into two main categories: input and output. Feeding (food administered and its nutritional characteristics) was considered as the input parameter. The output indicators were directly or indirectly correlated with feeding, and included: quality and quantity of milk, body condition score, live weight, reproductive parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Some more recent international applications of production economics include those of André et al (2010) who examined the profit-maximising amount of concentrate to feed cows in confined systems and those of Adduci et al (2015) who developed a model to evaluate the efficiency of dairy cow rations. A limitation to applying the productioneconomics approach in grazing systems has been the lack of milk-response functions.…”
Section: Economic Framework To Reliably Assess Tactical Feeding Manamentioning
confidence: 99%
“…Some more recent international applications of production economics include those of André et al (2010) who examined the profit-maximising amount of concentrate to feed cows in confined systems and those of Adduci et al (2015) who developed a model to evaluate the efficiency of dairy cow rations. A limitation to applying the productioneconomics approach in grazing systems has been the lack of milk-response functions.…”
Section: Economic Framework To Reliably Assess Tactical Feeding Manamentioning
confidence: 99%
“…Moreover, Hall (2002) reported that the high presence of faeces in the first two score classes was directly related to unbalanced rations in terms of protein. On the contrary, an increase of categories 4 and 5 (high consistency) was observed in farms characterized by fibre excess and low water intake (Adduci et al, 2015). The consistency of manure is a function of the feed moisture content and the mean retention time of the feed in the digestive tract of the animal (Varga, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that can significantly contribute to fluctuations in cattle finishing cost of gains and profits include changes in cattle prices, feed prices, and performance. Adduci et al [12] reports that the practical approach for economic and technical evaluation of the food rationing allowed to identify, to highlight, and to confirm important criticalities caused by incorrect feeding management. Schroeder et al [13] finds that approximately 93% of the variability in cost of gain over time can be explained by changes in corn prices, feed conversions, and daily gains.…”
Section: Riskmentioning
confidence: 99%